Constrained CMA-Based Blind Multiuser Detection for DS-CDMA UWB in a Realistic Indoor Channel - Zhengqiang Wang; Ming Zhao; Xin-e Li (2011 Fifth International Conference on Genetic and Evolutionary Computing, 2011)
In this paper, a linearly constrained constant modulus algorithm (LCCMA) based blind adaptive multi-user detection for DS-UWB system is presented in a realistic indoor channel. Based on gradient descent method, The key problem to minimizing the CMA cost function subject to multiple linear constraints is pre-selected or jointly updated. Theoretical analysis and simulation results show that, compared with the training sequence based adaptive MUD, the proposed scheme can increase the transmission capacity, and then can be considered as a compromise candidate for indoor DS-UWB high data rate multi-user access scenarios.